ROLE OF FOOD ASSISTANCE IN DIABETES MANAGEMENT AMONG LOW-INCOME SENIORS. (11th November 2018) - Alford, S; Warren, A; Frongillo, E
Abstract: Senior food insecurity and seniors' heterogeneous needs and experiences have prompted development of innovative, senior-focused programs intended to support healthy aging, led by food banks in the national Feeding America network. A large proportion of seniors participating in food assistance programs are diabetic or pre-diabetic with dietary needs not typically met by non-targeted and senior-focused food assistance programs. This study aimed to 1) describe how low-income diabetic seniors perceive their dietary needs, and 2) understand how seniors perceive the relationship between food assistance and their ability to manage their diabetes in the context of four senior-focused food assistance programs. Data for aim 1 were from semi-structured, qualitative interviews with 51 seniors who self-reported as diabetic across 9 US states. Data for aim 2 were from 23 seniors participating in 4 food assistance programs across 4 US states that provided lean proteins, whole grains, and fresh produce to respond to dietary needs. Diabetic seniors perceived needing to consume more fresh and canned produce and lean protein and fewer items high in carbohydrates and added sugar. The majority of seniors reported being unable to afford produce and protein consistently or at all. Seniors in the 4 programs valued the inclusion of healthier foods, particularly fresh produce, and reported that the program enabled them to consume more of these foods. Food-insecure seniors reported improved ability to manage their diabetes upon participating in the programs. Senior-focused, food assistance programs should and can tailor food to be responsive to diabetes to support healthy aging.